Economic Violence Against Women: A Case in the National Capital Region (NCR) - Yao, Myrna Tang; Tanigue, Yolanda; Galang, Glenn Mhar (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Economic abuse has a deeper and more lasting impact on women than on men, severely affecting their financial stability, independence, and ability to make life choices. It often involves control over their money, employment, property, and education. A study conducted in the National Capital Region examined women's experiences of economic abuse, using three groups: Inner Wheel Club members, SSS personnel, and LGU employees, each sampled with different methods. The findings revealed that economic abuse prevents many women from starting or managing businesses, keeping jobs, or making independent decisions. Common forms include financial control, workplace sabotage, and theft of money or resources. Some women were burdened with debts in their or their children’s names. The study recommends a law requiring husbands to financially support their wives and families, with penalties for non-compliance. Agencies like the PNP, DSWD, and the judiciary should enforce this law. Support measures should include providing women and children with shelter and essentials during legal proceedings and restricting abusive husbands’ access to their wives during trials. Women should also have legal access to financial records, shared accounts, and property. These protections are essential to restore women's financial autonomy and protect them from further harm.